Synthetic Curcumin Analog UBS109 Inhibits the Growth of Head and Neck Squamous Cell Carcinoma Xenografts - Zhu, Shijun; W. Moore, Terry; Morii, Nao; B. Howard, Randy; F. Arrendale, Richard; Reddy, Prabhakar; J. Evers, Taylor; Zhang, Hongzheng; Sica, Gabriel; G. Chen, Zhuo; Sun, Aiming; Fu, Haian; et al. (Current Cancer Drug Targets, 2014)
The natural compound curcumin has been investigated as an anticancer agent in many cellular systems, in animal models and in the clinic. The overriding negative characteristics of curcumin are its low solubility, weak potency and poor bioavailability. We have examined the efficacy and mechanism of action of a synthetic curcumin analog, UBS109, in head and neck squamous cell carcinoma. By nephelometry, this analog exhibits considerably greater solubility than curcumin. Pharmacokinetic studies of a single oral dose of UBS109 in mice revealed that peak plasma concentrations were reached at 0.5 hours post-dose (Tmax) with average plasma concentrations (Cmax) of 131 and 248 ng/mL for oral doses of 50 and 150 mg/kg, respectively. The terminal elimination half-lives (T½) for these doses averaged 3.7 and 4.5 hours, respectively. In both in vitro and in vivo studies, we found that UBS109 decreased the levels of phosphorylated IKKβ and phosphorylated p65 and, unexpectedly, increased the levels of phosphorylated IκBα by Western blot analysis. These observations may suggest that UBS109 suppresses tumor growth through, in part, inhibition of NF-κB p65 phosphorylation by PKAc and not through IκBα. Finally, we demonstrate that UBS109 is efficacious in retarding the growth of Tu212 (head and neck) squamous cell carcinoma (SCC) xenograft tumors in mice and may be useful for treating head and neck SCC tumors.
Keywords: NF-κB p65 phosphorylation